Analysis of Different Factors Associated with Re-Laparotomy After Cesarean Section Deliveries at a Tertiary Care Hospital: A Retrospective Study - Breera Sadaf, Salma Khudaidad, Devi Kumari, Summiya Ramzan, Farzana Khan, Rubina Amjad, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To evaluate factors that are associated with re-laparotomy after cesarean section. Study design: Retrospective study Place and Duration: This study was conducted at Sheikh Zaid Hospital Quetta, Bolan Medical Complex Hospital Quetta, Jinnah Medical and Dental College karachi, Sandeman Provincial Hospital Quetta, Mekran Medical College Teaching Hospital Turbat Kech, Pakistan from the year 2019 to 2021 Methodology: For this research interview sessions with patients were conducted. Clinical examinations were done and Bed Head ticket (BHT) was used for examining the medical history of patients. All the information related to age, parity, indications of caesarian section, and gestational age were observed including time interval of re-laparotomy from caesarian section. Furthermore, information related to clinical features of re-laparotomy, duration of re-laparotomy, and outcomes were also kept for statistical analysis. Results: Over two years, we observed 22192 cases of caesarian deliveries. Out of these 37 emergency caesarian required re-laparotomy procedure. We observed non-progress of labor as a major indication of LUCS in the primary caesarian section comprised of 21.62% of cases. Another dominion indication of the caesarian section was reported as CPD (5.40%), meconium stained liquor (MSL) with Bradycardia (10.81%), and PROM in 10.81% of cases. Rectus sheath hematoma was a major indication of re-laparotomy in 29.7% of cases while 27.02% of cases in our study reported peritoneal hemorrhage. Conclusion: Findings of our study revealed that unnecessary usage of caesarian surgery on patient leads to severe complications resulting in re-laparotomy. Factors like rectus sheath hematoma, Intra-peritoneal hemorrhage and abscess are the dominant reasons for re-laparotomy.